Prehistoric settlement patterns and cultures in Susiana, Southwestern Iran : the analysis of the F.G.L. Gremliza survey collection - Alizadeh, Abbas, 1951- (Technical reports (University of Michigan. Museum of Anthropology), 1992)
This book reports the results of an archaeological survey undertaken in southwestern Iran by a remarkable researcher: Dr. F.G.L. Gremliza. The author, Abbas Alizadeh, presents Gremliza's survey data and provides an analysis of the developmental implications.